Spillover effects of financial development on renewable energy deployment and carbon neutrality: Does GCC institutional quality play a moderating role? - Hamed, Wesam M. A.; Ozatac, Nesrin (Springer, 2024)
In the framework of sustainable ecology, financial sustainability takes on greater significance. As a result, this study examines the impact of financial development (bank adequacy) on both renewable energy and carbon emissions for Gulf Cooperation Council (GCC) countries from 2005 to 2020, using institutional quality (government stability and corruption control) as a moderating factor while controlling for FDI, population growth, and urbanization. However, for the investigation, the quantile-on-quantile regression technique was used, while the fixed effect OLS and Driscoll Kraay OLS techniques were used as robustness checks. The first model outcome reveals that all the variables have a positively significant connection with renewable energy. This implies that higher bank capital adequacy-augmented liquid assets, heightened asset returns, and enhanced investment viability. prospects may encourage physical asset outlays of companies operating in greening. But for the second model, financial development, FDI, and government stability have a positive relationship with carbon emissions, which confirms the presence of the pollutant haven hypothesis for the understudied countries while controlling corruption, population, and urbanization to decrease ecological degradation. This outcome implies that excess-investment clean energy enterprises intermediary effect of liquidity of banks for the understudy countries. Moreover, this study adds to the current literature by comparing the financial development (capital adequacy of banks) in GCC countries that are leaders in climate finance and by highlighting the role that bank capital adequacy plays in strengthening environmental laws to promote investment in renewable energy.
Keywords: Financial development; Bank adequacy; Renewable energy; Carbon emission; Institution quality; GCC countries